Summer phytoplankton photosynthetic characteristics in the Changjiang River Estuary and the adjacent East China Sea - Li, Ji; Gao, Yonghui; Bao, Yalin; Gao, Xiu; Glibert, Patricia M. (Frontiers in Marine Science, 2023)
Introduction The Changjiang (Yangtze) River is one of the largest rivers in the world, and its estuary and offshore plume create a diversity of ecological habitats for the phytoplankton community. The phytoplankton community has to balance between light limitation in the sediment-laden inshore waters and nutrient limitation in the offshore waters. Active fluorescence measurements can provide rapid, non-intrusive estimates of photosynthetic characteristics at high spatial and temporal resolution. Methods In the summer of 2020, a field survey of hydrodynamic characteristics, availability of nutrients, the maximum quantum efficiency of photosystem II (Fv/Fm), and rapid light curves across the Changjiang River Estuary and its adjacent sea was conducted, assessing relationships between photosynthetic physiology and biomass accumulation. Results The photosynthetic activities significantly differed among the turbid river water, the stratified river plume water, and the oceanic East China Sea Water. The photosynthetic physiology of phytoplankton was the most active near the front of Changjiang Diluted Water, where the Fv/Fm was over 0.5. Discussion Phytoplankton photosynthesis was alleviated from light limitation downstream of the river mouth, and benefited from phosphorus supply via tidal mixing and upwelling. The relatively suitable light and nutrients led to high photosynthetic activities, supporting increased productivity and biomass in this water. The phytoplankton in the Changjiang estuary rivermouth were under intense stress, suggested by the Fv/Fm values under 0.3. Also, the strong vertical mixing process diluted the river nutrients before the phytoplankton consumed them. Nutrients further limited the phytoplankton offshore in the East China Sea.